PERILAKU KONSUMTIF DITINJAU BERDASARKAN FANATISME, GAYA HIDUP BRAND MINDED DAN KONTROL DIRI - Rabiatul Adhawiyah; Achmad Ruslan Afendi; Hardiansyah Hardiansyah (Institut Pendidikan Tapanuli Selatan, 2023)
This study aims to determine consumptive behavior in terms of the influence of fanaticism, brand minded lifestyle and self-control on University X students. This study uses a quantitative approach with a total of 221 students selected by purposive sampling technique. The data was collected using a Likert-type scale which was then analyzed using the Structural Equation Modeling (SEM) method with the help of Amos software version 22. The results showed that fanaticism had an influence on student consumptive behavior with a C.R value of 3.511 1.96 and a p value of 0.000 < 0.05. Then the brand minded lifestyle has no influence on consumptive behavior with a C.R value of -1.807 1.96 and a p value of 0.071 > 0.05. Furthermore, self-control has an influence on consumptive behavior with a C.R value of -4.433 1.96 and a p value of 0.000 <0.05